Adoption of smart-valley approach by rice producers in Benin, Togo, Nigeria, Liberia and Sierra Leone (Liberia and Sierra Leone are two new countries in 2020) - CGIAR Research Program on Rice (2020)
Adoption of smart-valley increased from 110 ha in 2012 to 474 ha in 2014. Recent evidence show the approach has reached 45,000 ha in Nigeria. In 2019, the total area increased to 1030.94 hectares in Benin and Togo and adopted by 6110 farmers. In Sierra Leone, the total area tracked was 179.3 hectares and adopted by 460 rice farmers. Results show that the impact of the smart-valley on the rice income is 439.65 US$/ha in Sierra Leone & Liberia